2019
DOI: 10.1111/eip.12905
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to age inclusive early intervention for psychosis

Abstract: Aim: Early Intervention in psychosis Services (EIS) have previously restricted access based on age. However, there is now a move to age inclusive service. We aimed to examine differences between early and late onset (>35 years) psychosis to see if a threshold was valid. We also investigated the potential of a statistical modelling method to identify group characteristics which may be missed using a descriptive approach. Method: Routine clinical data (n=343), from an EIS, comprising sociodemographic, clinical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
3
8
2
Order By: Relevance
“…While only a small proportion of both age groups had HoNOS data available at pre-and post-service use, those who did showed significant improvement in HoNOS scores overall, and for the individual items including self-injury, cognitive problems, hallucinations, other mental health problems, relationship problems and occupational problems. This finding is in line with previous research suggesting EI services are beneficial (Bird et al, 2010;Correll et al, 2018;Fusar-Poli et al, 2017), and studies demonstrating improved outcomes following EI service use for both under and over 35s (Lappin et al, 2016;Lasalvia et al, 2017;O'Driscoll et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While only a small proportion of both age groups had HoNOS data available at pre-and post-service use, those who did showed significant improvement in HoNOS scores overall, and for the individual items including self-injury, cognitive problems, hallucinations, other mental health problems, relationship problems and occupational problems. This finding is in line with previous research suggesting EI services are beneficial (Bird et al, 2010;Correll et al, 2018;Fusar-Poli et al, 2017), and studies demonstrating improved outcomes following EI service use for both under and over 35s (Lappin et al, 2016;Lasalvia et al, 2017;O'Driscoll et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…care coordinators), interpreted to indicate more complexity, and greater clinical and social needs (Jagger et al, 2019). Another found no differences in clinical outcomes, despite variation in social factors between the age groups (O'Driscoll et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long durations of untreated psychosis have been reported in Sub-Saharan Africa compared to high income countries and have been associated with poorer outcomes [54][55][56]. Late onset of psychotic illnesses is often associated with a less severe course and better outcomes [57]. This is important for future intervention programs given that both DUP and late onset illness psychosis have different outcome trajectories [14,53,58].…”
Section: Age Of Initial Presentation With a First Episode Of Psychosismentioning
confidence: 99%
“…Substance misuse, being male, low socioeconomic status and belonging to an ethnic minority, are risk factors associated with poorer functioning over time. A previous EIS study (O'Driscoll et al, 2019) exploring intensive care identified living in supported accommodation and specific healthrelated factors (BMI, smoking status and age) were related to increased utilisation (hospitalisations and crisis team episodes). The literature to date has explored trajectories across short time scales (one to two years) rather than covering the 3-years of EIS support and pertain to social functioning as an outcome rather than care provision.…”
Section: Introductionmentioning
confidence: 95%